Specific antibody-DNA interaction: a novel strategy for tight DNA recognition. - Di Pietro, Santiago M. (2003)
Anti-double-stranded DNA monoclonal antibodies against a viral transcriptional regulatory site are capable of discriminating single-base replacements with affinities of 1 x 10(-9) M, which were optimized for the length of the duplex used as the immunogen. Their affinity for DNA duplexes of increasing length is lower, but reaches a plateau at 2 x 10(-8) M, still a fairly high affinity compared to those of most known natural anti-DNA antibodies. The ability of the antibodies to bind to a 166 bp DNA fragment containing the specific sequence strongly suggests that these have the potential of binding the specific sequence within larger genomic DNA fragments. Electrostatic interactions do not play a significant role, the opposite of what is observed in natural DNA binding interfaces. In addition, the insensitivity of the antibody-DNA interaction to solute effects is indicative of a marginal participation of water molecules at the interface compared to the level of participation at the natural E2-DNA interface. Spectroscopic evidence of base unstacking strongly suggests substantial denaturation of antibody-bound DNA, in agreement with thermodynamic results that show an unusual positive heat capacity change, which could be explained at least in part by the exposure of DNA bases upon binding. Lower local DNA stability cooperates with sequence recognition in producing the highest binding affinity. A slow rate of antibody-DNA association indicates an energy barrier imposed by conformational rearrangements, as opposed to an electrostatically assisted diffusion-controlled collision in the E2 DNA binding domain. While the E2-DNA interaction takes place through a typical direct readout mechanism, the anti-double-stranded DNA monoclonal antibody-DNA interaction could be viewed as a distinctive case of indirect readout with a significant distortion in the DNA conformation. However, the precise mechanism with which the DNA bases are accommodated in the antibody combining site will require structural analysis at atomic resolution. These results constitute a first stage for unveiling the unusual molecular recognition mechanism of a specific DNA sequence by antibodies. This mechanism could represent the strategy with which the immune system tightly and specifically recognizes a DNA antigen.